Ultra-high performance concrete for tower piece of wind power mixed tower and preparation method of ultra-high performance concrete
By using specific proportions of components and admixtures in ultra-high performance concrete, the problems of insufficient crack resistance and insufficient early strength of precast concrete in the existing technology are solved, and higher crack resistance and early strength are achieved, which improves production efficiency and reduces costs.
Patent Information
- Application Number
- CN202411665100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing ultra-high performance concrete is insufficient in the ultra-high wind power tower connection conversion section, and the precast concrete has insufficient early strength and working performance, which affects production efficiency and cost.
Ultra-high performance concrete consisting of cement, quartz sand, microbeads, silica fume, fly ash, steel fibers, admixtures, water reducers and retarders are used to improve the hardness, wear resistance, compressive strength, crack resistance and early strength of the concrete through the combination of specific proportions of components and admixtures.
It significantly improves the crack resistance and early strength of concrete, enhances its durability and working performance, makes it more suitable for the connection conversion section of ultra-high wind power towers, improves the production efficiency of precast concrete and reduces production costs.
Smart Images

Figure BDA0005144399840000041 
Figure BDA0005144399840000051 
Figure BDA0005144399840000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to an ultra-high performance concrete for wind power hybrid tower segments and a preparation method thereof. Background Art
[0002] With the rapid development of the wind power industry, the performance requirements for wind turbine towers are getting higher and higher. Ultra-high performance concrete (UHPC) has become an ideal choice for wind turbine tower materials due to its excellent mechanical properties, durability and working performance.
[0003] The connection and conversion section of a wind turbine tower is subjected to complex forces and has higher requirements for crack resistance. The existing ultra-high performance concrete can meet the crack resistance requirements of the connection and conversion section of a wind turbine tower of general specifications, but for ultra-high wind turbine towers, the crack resistance of the existing ultra-high performance concrete needs to be further improved.
[0004] In addition, in order to speed up the mold turnover rate and improve the production efficiency of enterprises, the wind power industry requires precast concrete not only to have high strength and good durability, but also high early strength, good construction performance, and ultra-long operability time, so as to further speed up the construction progress, shorten the construction period, and improve economic benefits. Therefore, improving the early strength and working performance of concrete is an effective technical way to improve the production efficiency of precast concrete wind power tower components and reduce production costs. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an ultra-high performance concrete for wind power hybrid tower segments and a preparation method thereof.
[0006] The present application discloses an ultra-high performance concrete, which specifically comprises the following components in parts by weight: 800-920 parts of cement, 1000-1200 parts of quartz sand, 90-130 parts of microspheres, 100-140 parts of silica fume, 40-60 parts of fly ash, 145-170 parts of steel fiber, 10-20 parts of admixture, 9-13 parts of water reducer, 4-8 parts of retarder, and 140-175 parts of water; The quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1-5:1-5; The steel fiber has a diameter of 0.18-0.22 mm and an aspect ratio of ≤65; The additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin.
[0007] The present application selects quartz sand composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1-5:1-5, an admixture obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin, and mixes it with steel fibers of specific specifications and other raw materials in specific weight portions. The prepared concrete has good working performance, excellent slump expansion performance, can be self-flowing and compacted, and also has high early strength. The concrete prepared in the present application has good crack resistance and better durability.
[0008] The application utilizes the addition of quartz sand of different specifications to significantly improve the hardness and wear resistance of concrete; quartz sand has high hardness and excellent wear resistance, which enables it to act as an aggregate in concrete, enhancing the compressive strength and durability of concrete. At the same time, the chemical stability of quartz sand can also resist chemical reactions that may occur in concrete, thereby maintaining the stability of the concrete structure.
[0009] The introduction of steel fibers has brought significant toughening effects to concrete. Steel fibers are distributed in concrete to form a mesh structure. When concrete is subjected to external forces, these steel fibers can effectively prevent the expansion of cracks and improve the crack resistance of concrete. In addition, steel fibers can also enhance the tensile strength and impact resistance of concrete, making concrete show better toughness and durability when subjected to dynamic loads.
[0010] The addition of calcined magnesium oxide in the admixture of the present application can significantly improve the early strength and anti-cracking mechanical properties of concrete. Under different environments, calcined magnesium oxide can remain stable, effectively prevent the destruction of concrete structure, better resist the erosion of the external environment, maintain long-term firmness and beauty, thereby extending the service life of the building. Secondly, the introduction of hydroxyethyl cellulose brings better viscosity and water retention to concrete, improves the operability during the construction process, and makes the prepared concrete have good working performance, excellent slump expansion performance, and can be self-flowing and compacting molding; at the same time, its good water retention performance helps to reduce the water loss of concrete during transportation and pouring, and ensures the quality of concrete. In addition, the addition of ABS resin gives concrete excellent water absorption performance; during the hardening process of concrete, the super absorbent resin can absorb and store a large amount of water, and then gradually release it when needed, providing continuous maintenance for concrete; this unique water absorption performance helps to reduce the cracks caused by drying of concrete, and improves the anti-cracking performance, durability and overall performance of concrete.
[0011] Preferably, the ultra-high performance concrete specifically comprises the following components in parts by weight: 840-880 parts of cement, 1050-1150 parts of quartz sand, 100-120 parts of microspheres, 110-130 parts of silica fume, 45-55 parts of fly ash, 150-165 parts of steel fiber, 13-18 parts of admixture, 10-12 parts of water reducer, 5-7 parts of retarder, and 150-165 parts of water.
[0012] Preferably, the quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 4-5:1-2.
[0013] Preferably, the steel fiber is composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 10-20:1-3.
[0014] Preferably, the steel fiber is composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 13-17:1.5-2.5.
[0015] Through experimental analysis, it can be known that the application selects the steel fibers with the above weight ratio to prepare concrete, which can further improve the performance of the concrete.
[0016] Preferably, the additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin in a weight ratio of 8-14:1-5:0.2-0.8.
[0017] Preferably, the additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin in a weight ratio of 10-12:2-4:0.4-0.6.
[0018] In some specific embodiments, the weight ratio of the calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin can also be 8:1:0.5, 10:1:0.5, 11:1:0.5, 12:1:0.5, 14:1:0.5, 10:2:0.5, 11:2:0.5, 12:2:0.5, 14:2:0.5, 8:3:0.5, 10:3:0.5, 11:3:0.5, 12:3:0.5, 14:3:0.5, 10:4:0.5, 11:4:0.5, 12:4:0.5, 14:4:0.5, 10:5:0 .5, 11:5:0.5, 12:5:0.5, 10:1:0.2, 11:1:0.2, 12:1:0.2, 14:1:0.2, 8:2:0.4, 10:2:0.4, 11:2:0.4, 12:2:0.4, 8:3:0.5, 10:3:0.5, 11:3:0.5, 12:3:0.5, 8:4:0.6, 10:4:0.6, 11:4:0.6, 12:4:0.6, 8:5:0.8, 10:5:0.8, 11:5:0.8, 12:5:0.8, 14:5:0.8.
[0019] Through experimental analysis, it can be known that the present application selects calcined magnesium oxide, hydroxyethyl cellulose and ABS resin in the above weight ratio as admixtures for preparing concrete, which can further improve the performance of concrete.
[0020] Preferably, the preparation method of calcined magnesium oxide comprises: mixing magnesium carbonate, konjac flour and water in a weight ratio of 10-15:0.5-1.5:50, reacting at 50-70°C for 8-16h, then drying, and calcining at 500-650°C for 2-4h to obtain the calcined magnesium oxide.
[0021] Preferably, the particle size of the microbeads is ≤10 μm and the bulk density is 0.7 kg / cm 3 The average particle size of the silica fume is 0.15 μm, and the SiO2 content is ≥ 88%; the water reducer is HS-209 polycarboxylic acid water reducer; the retarder is sodium gluconate.
[0022] In a second aspect, the present application provides a method for preparing the above-mentioned ultra-high performance concrete, which specifically comprises the following steps in sequence: Weigh the corresponding weights of the raw material components respectively, add cement, quartz sand, microspheres, silica fume, fly ash, steel fiber into water, mix evenly, then add admixtures, retarders, and water reducers, stir and mix evenly, and after curing, the ultra-high performance concrete is obtained.
[0023] In summary, the technical solution of this application has the following effects: The present application selects quartz sand composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1-5:1-5, an admixture obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin, and mixes it with steel fibers of specific specifications and other raw materials in specific weight portions. The prepared concrete has good working performance, excellent slump expansion performance, can be self-flowing and compacted, and also has high early strength. The concrete prepared in the present application has good crack resistance and durability. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.
[0025] The cement used in this application is P·O 42.5 cement; the particle size of the microbeads is ≤10μm, and the bulk density is 0.7kg / cm 3 The average particle size of silica fume is 0.15μm, and the SiO2 content is ≥88%. The fly ash adopts F-class II fly ash with a fineness of 15.6%, a water requirement of 97%, and a loss on ignition of 3.8%. The copper-plated fine high-strength steel fiber has a tensile strength of ≥2500MPa, a length of ≤13mm, and a diameter of 0.18-0.22mm. Hydroxyethyl cellulose and ABS resin are purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the water reducer is HS-209 polycarboxylic acid water reducer; the retarder is sodium gluconate; konjac extract is purchased from Fenhexing Biotechnology Co., Ltd.; the remaining raw materials can be obtained commercially. Example
[0026] Examples 1-3 Examples 1-3 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0027] The difference between the above embodiments is that the dosage of each component in the ultra-high performance concrete is different, as shown in Table 1.
[0028] The preparation method of the ultra-high performance concrete in the above embodiment is: Preparation of calcined magnesium oxide: magnesium carbonate is mixed with konjac flour and water in a weight ratio of 12:1:50, reacted at 60°C for 12 hours, then dried, and calcined at 600°C for 3 hours.
[0029] As shown in Table 1, the corresponding weights of the raw material components are weighed respectively, and cement, quartz sand (quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 4:1), microspheres, silica fume, fly ash, and steel fiber (composed of a mixture of steel fiber with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fiber with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 15:2) are added to water and mixed evenly, and then an admixture (the admixture is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose with a viscosity of 5500-6500 mpas, and ABS resin in a weight ratio of 11:3:0.5), sodium gluconate retarder, and HS-209 polycarboxylate water reducer are added, stirred and mixed evenly, and the ultra-high performance concrete is obtained after curing.
[0030] Table 1 Amounts of each raw material component of ultra-high performance concrete in Examples 1-3 and Comparative Examples 1-2 Embodiment 4-7 Examples 4-7 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0031] The difference between the above embodiment and embodiment 2 is that the types of quartz sand are different, as shown below.
[0032] In Example 4, the quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 5:1.
[0033] In Example 5, the quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 4:2.
[0034] In Example 6: the quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1:4.
[0035] In Example 7: the quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1:1.
[0036] The other process parameters in the above embodiment are the same as those in embodiment 2.
[0037] Embodiment 8-11 Examples 8-11 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0038] The difference between the above embodiment and embodiment 2 is that the types of steel fibers are different, as shown below.
[0039] In Example 8: the steel fibers are composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 13:2.5.
[0040] In Example 9: the steel fibers are composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 17:1.5.
[0041] In Example 10: the steel fibers are composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 10:3.
[0042] In Example 11: the steel fibers are composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 20:1.
[0043] The other process parameters in the above embodiment are the same as those in embodiment 2.
[0044] Examples 12-16 Examples 12-16 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0045] The difference between the above embodiment and embodiment 2 is that the types of admixtures are different, as shown below.
[0046] In Example 12: The preparation method of calcined magnesium oxide is: magnesium carbonate is mixed with konjac flour and water in a weight ratio of 10:1.5:50, reacted at 50°C for 16 hours, then dried, and calcined at 600°C for 3 hours; the admixture is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin in a weight ratio of 8:5:0.8.
[0047] In Example 13: The preparation method of calcined magnesium oxide is: magnesium carbonate is mixed with konjac flour and water in a weight ratio of 15:0.5:50, reacted at 70°C for 8 hours, then dried, and calcined at 600°C for 3 hours; the admixture is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin in a weight ratio of 14:1:0.2.
[0048] In Example 14: the admixture is obtained by mixing magnesium carbonate, hydroxyethyl cellulose with a viscosity of 5500-6500 mpas, and ABS resin in a weight ratio of 11:3:0.5.
[0049] In Example 15: Preparation of calcined magnesium oxide: magnesium carbonate is calcined at 600°C for 3 hours; the admixture is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose with a viscosity of 5500-6500 mpas, and ABS resin in a weight ratio of 11:3:0.5.
[0050] In Example 16: Preparation of calcined magnesium oxide: magnesium carbonate is mixed with konjac flour and water in a weight ratio of 12:1:50, reacted at 60°C for 12 hours, then dried, and calcined at 600°C for 3 hours; the admixture is obtained by mixing calcined magnesium oxide in a weight ratio of 3:12:1.5, hydroxyethyl cellulose with a viscosity of 1000-1500mPa.s, and ABS resin.
[0051] The other process parameters in the above embodiment are the same as those in embodiment 2.
[0052] Comparative Example Comparative Example 1-2 Comparative Examples 1-2 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0053] The difference between Comparative Example 1-2 and Example 2 is that the amounts of the components in the ultra-high performance concrete are different, as shown in Table 1.
[0054] The other process parameters in the above comparative example are the same as those in Example 1.
[0055] Comparative Examples 3-6 Comparative Examples 3-6 respectively provide an ultra-high performance concrete and a preparation method thereof.
[0056] The differences between Comparative Examples 3-6 and Example 2 are specifically as follows.
[0057] In Comparative Example 3: the quartz sand is composed of a mixture of 5-15 mesh sand and 100-150 mesh sand in a weight ratio of 5:1.
[0058] In Comparative Example 4: the diameter of the steel fiber is 0.18-0.22 mm, and the aspect ratio is 65-85.
[0059] In Comparative Example 5: an equal amount of basalt fiber (basalt fiber with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65) was used to replace the steel fiber.
[0060] In Comparative Example 6: the admixture is obtained by mixing calcined magnesium oxide and hydroxyethyl cellulose in a weight ratio of 11:3.
[0061] The other process parameters in the above comparative example are the same as those in Example 1.
[0062] Performance testing (1) Test the performance of concrete mixtures according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". (2) The compressive strength and splitting tensile strength of concrete are measured in accordance with GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete".
[0063] (3) Simulate the complex stress of the wind turbine tower connection conversion section on the concrete and observe the cracks on the wall.
[0064] (4) Aging resistance (80°C, 720 h): The concrete specimens were placed at 80°C for 720 h. The splitting tensile strength of the concrete was measured according to GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". Aging resistance = splitting tensile strength after aging test / 28d splitting tensile strength of the original specimen × 100%.
[0065] Test results: as shown in Table 2.
[0066] Table 2 Test results of concrete in the embodiments and comparative examples From the performance test results of the concrete in the examples and comparative examples in Table 2, it can be seen that the concrete prepared using the technical solution of the present application has very good working performance, excellent slump expansion performance representing filling and gap passability, can be self-flowing and compacted, and also has very high early strength, with a 3d compressive strength greater than 43 MPa, and the concrete prepared in the present application has good crack resistance and better durability.
[0067] By comparing the test results of Examples 1-3 with those of Comparative Examples 1-2, it can be seen that the amount of each raw material component in concrete has a great influence on the performance of concrete. The present application significantly improves the performance of concrete by reasonably controlling the amount of each raw material component.
[0068] By comparing the test results of Example 2 and Comparative Example 3, it can be seen that the present application utilizes a quartz sand raw material composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1-5:1-5, which significantly improves the performance of concrete; further, the present application controls the quartz sand to be composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 4-5:1-2.
[0069] By comparing the test results of Example 2 with those of Comparative Examples 4-5, it can be seen that the present application utilizes a steel fiber composed of a steel fiber having a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 mixed with a steel fiber having a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 10-20:1-3, which significantly improves the performance of concrete.
[0070] By comparing the test results of Example 2 with those of Comparative Example 6, it can be seen that the present application utilizes an admixture obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose, and ABS resin in a weight ratio of 8-14:1-5:0.2-0.8, which significantly improves the performance of concrete.
[0071] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An ultra-high performance concrete, characterized in that: Specifically, it includes the following components in parts by weight: 800-920 parts of cement, 1000-1200 parts of quartz sand, 90-130 parts of microspheres, 100-140 parts of silica fume, 40-60 parts of fly ash, 145-170 parts of steel fiber, 10-20 parts of admixture, 9-13 parts of water reducer, 4-8 parts of retarder, and 140-175 parts of water; The quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 1-5:1-5; The steel fiber has a diameter of 0.18-0.22 mm and an aspect ratio of ≤65; The additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin.
2. The ultra-high performance concrete according to claim 1, characterized in that: Specifically, it includes the following components in parts by weight: 840-880 parts of cement, 1050-1150 parts of quartz sand, 100-120 parts of microspheres, 110-130 parts of silica fume, 45-55 parts of fly ash, 150-165 parts of steel fiber, 13-18 parts of admixture, 10-12 parts of water reducer, 5-7 parts of retarder, and 150-165 parts of water.
3. The ultra-high performance concrete according to claim 1, characterized in that: The quartz sand is composed of a mixture of 20-40 mesh quartz sand and 40-70 mesh quartz sand in a weight ratio of 4-5:1-2.
4. The ultra-high performance concrete according to claim 1, characterized in that: The steel fiber is composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 10-20:1-3.
5. The ultra-high performance concrete according to claim 1, characterized in that: The steel fiber is composed of a mixture of steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 35-65 and steel fibers with a diameter of 0.18-0.22 mm and an aspect ratio of 10-30 in a weight ratio of 13-17:1.5-2.
5.
6. The ultra-high performance concrete according to claim 1, characterized in that: The additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin in a weight ratio of 8-14:1-5:0.2-0.
8.
7. The ultra-high performance concrete according to claim 6, characterized in that: The additive is obtained by mixing calcined magnesium oxide, hydroxyethyl cellulose and ABS resin in a weight ratio of 10-12:2-4:0.4-0.
6.
8. The ultra-high performance concrete according to claim 6, characterized in that: The preparation method of calcined magnesium oxide comprises: mixing magnesium carbonate, konjac powder and water in a weight ratio of 10-15:0.5-1.5:50, reacting at 50-70°C for 8-16h, drying, and calcining at 500-650°C for 2-4h to obtain the calcined magnesium oxide.
9. The ultra-high performance concrete according to claim 1, characterized in that: The particle size of the microbeads is ≤10µm and the bulk density is 0.7kg / cm 3 ; The average particle size of the silica fume is 0.15 μm and the SiO2 content is ≥ 88%; the water reducer is HS-209 polycarboxylic acid water reducer; the retarder is sodium gluconate.
10. The method for preparing ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: Specifically, the following steps are performed in sequence: Weigh the corresponding weights of the raw material components respectively, add cement, quartz sand, microspheres, silica fume, fly ash, steel fiber into water, mix evenly, then add admixtures, retarders, and water reducers, stir and mix evenly, and after curing, the ultra-high performance concrete is obtained.
Citation Information
Patent Citations
High-fluidity high-adhesion shrinkage compensation UHPC and preparation method thereof
CN110981358A
Special cementing agent for self-curing pervious concrete and application thereof
CN111116088A
Ultra-high performance concrete prefabricated part and preparation method thereof
CN115093183A
Ultra-high performance concrete material
CN117735918A
Ultra-high performance nano-modified concrete composition with borosilicate glass lamp waste powder
EP2837609A1